(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article analyzes the factors contributing to the decrease in hemoglobin levels, specifically the onset of anemia, in preschool children (aged 0–5) and its correlation with malnutrition. The paper provides a scientific and theoretical exploration of factors such as the mechanisms of iron deficiency formation in the child’s body, inadequate and unbalanced diets, micronutrient deficiencies, and the nutritional literacy of parents. Furthermore, based on the perspectives of various scientists in the fields of child physiology, pediatrics, and nutritional hygiene, approaches aimed at preventing hemoglobin decline are analyzed. The importance of establishing a healthy nutrition system for children, incorporating iron-rich foods, and implementing preventive measures is justified. The findings hold significant scientific and practical value for improving the health of preschool children.